Hamodactylus macrophthalmus spec. nov., a new coral-associated pontoniine shrimp (Decapoda, Caridea, Palaemonidae) from Indonesia - Fransen, Charles H.j.m.; Rauch, Cessa (Zootaxa, 2013)
A new coral-associated species of the genus Hamodactylus is described fromLembeh Strait,NESulawesi,Indonesia. The three other known species in the genus have been recorded in association with octocorals. The single ovigerous female specimen of the new species was collected from a scleractinian host. It can be easily separated from its congeners by the very long eyestalks and the chela of the second pereiopods having blunt tips of the fingers with tufts of long simple setae giving it an atyid-like appearance.